Konsep pembelajaran bahasa arab untuk mahasiswa non- arab - mardlatillah, wafiq zain (Maliki Interdisciplinary Journal, 2026)
Learning Arabic can be tough for students who aren’t Arab, and there are many reasons why. These include language barriers, feelings of doubt, and not being exposed to real Arabic conversations. This study looks at ways to help these students learn Arabic better by looking at basic ideas, learning strategies, and teaching methods. The research shows that learning Arabic step by step, using real-life situations, combining different language skills, focusing on communication, and putting the student in the center are important for making learning meaningful and lasting. Developing skills like listening, speaking, reading, and writing needs a practical approach that includes videos, pictures, and real-life materials. Using grammar and sentence structure in real practice is better than just learning from books. Also, tools like online learning sites, vocabulary apps, and teaching videos help students speak and understand better. Teaching styles like working in groups, doing tasks, doing projects, and mixing online and classroom learning make learning more active, helpful, and connected to real life. environments. Overall, the study concludes that Arabic language learning for non-Arab students becomes more effective when designed adaptively, innovatively, and based on learners’ needs.